2022
DOI: 10.3390/metabo12070639
|View full text |Cite
|
Sign up to set email alerts
|

Reconnoitering the Therapeutic Role of Curcumin in Disease Prevention and Treatment: Lessons Learnt and Future Directions

Abstract: Turmeric is a plant with a very long history of medicinal use across different cultures. Curcumin is the active part of turmeric, which has exhibited various beneficial physiological and pharmacological effects. This review aims to critically appraise the corpus of literature associated with the above pharmacological properties of curcumin, with a specific focus on antioxidant, anti-inflammatory, anticancer and antimicrobial properties. We have also reviewed the different extraction strategies currently in pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 289 publications
(232 reference statements)
0
16
0
Order By: Relevance
“…The improvement of toxic therapeutics’ delivery to cancerous tissue through the use of nanocarriers as chemotherapeutic delivery systems has been noted. To increase the solubility and stability of Cur, various kinds of nanocarriers have been created [ 3 ]. Cur can be made more stable, absorbed, and delivered to target sites by being encapsulated into bio-polymeric particles or conjugated with nanoparticles, for instance [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of toxic therapeutics’ delivery to cancerous tissue through the use of nanocarriers as chemotherapeutic delivery systems has been noted. To increase the solubility and stability of Cur, various kinds of nanocarriers have been created [ 3 ]. Cur can be made more stable, absorbed, and delivered to target sites by being encapsulated into bio-polymeric particles or conjugated with nanoparticles, for instance [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it did not exhibit any adverse effects even at higher doses and was found safe when administered to humans on a regular basis. Although low bioavailability of curcumin limits its therapeutic efficacy, several efforts have been made to enhance its bioavailability in the form of nanoformulations, using bio‐enhancers, and by synthesizing its water‐soluble derivatives (Sivani et al, 2022). In addition, its role as an adjuvant or in combination therapies has been found promising with reduced drug load and high efficacy in different clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…It induces apoptosis by activating caspase 3 and 9 expressions and reducing extracellular matrix-related protein expression [ 135 , 136 ]. Previous research has shown that curcumin has the ability to bind to progesterone receptors in semen, and reduce medroxyprogesterone acetate (MPA)-induced VEGF secretion in breast cancer cells containing estrogen and progesterone receptors [ 137 , 138 , 139 ]. However, evidence regarding curcumin’s modulation of progesterone receptors related to UFs is currently lacking.…”
Section: Natural Compounds That Can Benefit Against Uterine Fibroids ...mentioning
confidence: 99%